2023
DOI: 10.1001/jamanetworkopen.2023.27584
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Comorbidity Burden Among Women and Men With or At-Risk for HIV in the US, 2008-2019

Abstract: ImportanceDespite aging-related comorbidities representing a growing threat to quality-of-life and mortality among persons with HIV (PWH), clinical guidance for comorbidity screening and prevention is lacking. Understanding comorbidity distribution and severity by sex and gender is essential to informing guidelines for promoting healthy aging in adults with HIV.ObjectiveTo assess the association of human immunodeficiency virus on the burden of aging-related comorbidities among US adults in the modern treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Most important, we found that polypharmacy, especially hyperpolypharmacy, was associated with poor outcomes, including higher odds of slow gait speed and recurrent falls, even after adjusting for multimorbidity and other confounders. Although previous studies showed that women had higher rates of both polypharmacy and comorbidities [ 33–37 ], ours is the first to report that this association remained statistically significant after adjusting for the number of comorbidities. This suggests that the adverse effects of polypharmacy are not simply due to an accumulation of medical conditions but rather may reflect potential toxicities and other effects of numerous simultaneous medications, in addition to the effects of comorbidities.…”
Section: Discussionmentioning
confidence: 50%
“…Most important, we found that polypharmacy, especially hyperpolypharmacy, was associated with poor outcomes, including higher odds of slow gait speed and recurrent falls, even after adjusting for multimorbidity and other confounders. Although previous studies showed that women had higher rates of both polypharmacy and comorbidities [ 33–37 ], ours is the first to report that this association remained statistically significant after adjusting for the number of comorbidities. This suggests that the adverse effects of polypharmacy are not simply due to an accumulation of medical conditions but rather may reflect potential toxicities and other effects of numerous simultaneous medications, in addition to the effects of comorbidities.…”
Section: Discussionmentioning
confidence: 50%
“…30 Our analysis found elevated Elixhauser comorbidity scores in HIV-positive patients, relative to HIV-negative patients, in line with previous studies that posit greater comorbidity burden in individuals, and women in particular, who live with HIV. [31][32][33] In our assessment, Elixhauser comorbidity scores of three or fewer were protective against complications, whereas Elixhauser scores of four or more were associated with increased odds of complications. Likewise, Elixhauser scores above one were correlated with elevated odds of revision.…”
Section: Discussionmentioning
confidence: 63%
“…To date, there have been no studies evaluating the relationship between biologic sex and the development of PRISm among women with HIV despite the association of PRISm with increased mortality [ 4–6 ]. Evidence suggests that women with HIV are at higher risk for developing aging-related comorbidities compared with men [ 36 , 37 ]; the progression and development of lung function abnormalities within this group merit further study.…”
Section: Discussionmentioning
confidence: 99%